2017
DOI: 10.3390/cryst7100316
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation and Hydrogen Storage Properties of an La7.0Mg75.5Ni17.5 Hydrogen Storage Alloy

Abstract: X-ray diffraction showed that an La 7.0 Mg 75.5 Ni 17.5 alloy prepared via inductive melting was composed of an La 2 Mg 17 phase, an LaMg 2 Ni phase, and an Mg 2 Ni phase. After the first hydrogen absorption/desorption process, the phases of the alloy turned into an La-H phase, an Mg phase, and an Mg 2 Ni phase. The enthalpy and entropy derived from the van't Hoff equation for hydriding were −42.30 kJ·mol −1 and −69.76 J·K −1 ·mol −1 , respectively. The hydride formed in the absorption step was less stable tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…As shown in Figure 1, after years of research, various of solid hydrogen storage materials have been researched, including metal alloys [8] [9] [10], chemical Figure 1. Overview of some MH with their volumetric and gravimetric H-density [17].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, after years of research, various of solid hydrogen storage materials have been researched, including metal alloys [8] [9] [10], chemical Figure 1. Overview of some MH with their volumetric and gravimetric H-density [17].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of dislocations on phase transformation was examined by Hu et al [10], in which they studied phase transformation and hydrogen storage properties of an La 7.0 Mg 75.5 Ni 17.5 hydrogen storage alloy. Differential thermal analysis showed that the initial hydrogen desorption temperature of its hydride was 531 K and, compared to Mg and Mg 2 Ni, La 7.0 Mg 75.5 Ni 17.5 was found to be a promising hydrogen storage material that demonstrates fast adsorption/desorption kinetics as a result of the formation of an La − H compound.…”
mentioning
confidence: 99%